Криптоспоридіоз великої рогатої худоби (поширення, діагностика та заходи боротьби) - Журенко, Віталій Васильович (НУБіП України, 2017)
Дисертація на здобуття наукового ступеня кандидата ветеринарних наук зі спеціальності 16.00.11 «Паразитологія». – Національний університет біоресурсів і природокористування України, Київ, 2017. У дисертації викладено дані щодо поширення криптоспоридіозу в умовах господарств Київської та Житомирської областей України, їх вікової та сезонної динаміки. Визначено рівень інвазованості тварин криптоспоридіями. Встановлено вид збудника, яким є Cryptosporidium parvum. Відмічено максимальну ураженість телят криптоспоридіями у зимово-весняний період. Доведено, що ураженість тварин збудником криптоспоридіозу залежить від їх віку. Проведено порівняльний аналіз методів лабораторних досліджень. Підтверджено високу ефективність методу зажиттєвої діагностики криптоспоридіозу телят – фарбування мазків фекалій з сафраніном за Кестером. Встановлено його переваги порівняно з іншими методами фарбування. Визначено ефективність та проведено порівняльний аналіз толтароксу і толтароксу з імунобактерином-D. Досліджено вплив лікарських засобів на морфологічні, біохімічні та імунологічні показники крові телят. Запропоновано загальні та спеціальні заходи профілактики криптоспоридіозу великої рогатої худоби.
Thesis for a Candidate’s Degree in Veterinary Science, specialty 16.00.11 Parasitology. – National University of Life and Environmental Sciences of Ukraine, Kyiv, 2017. This paper is focuses on the study of Cryptosporidiosis in cattle. The thesis also presents data concerning with Cryptosporidiosis expansion on the conditions of farming in the northern-west of the Ukrainian region, regarding their age and season dynamics. The level of Cryptosporidiosis invasion in cattle was defined. The type of Cryptosporidium parvum agent was fixed. It was noticed that maximum lesion in calves with Cryptosporidiosis usually occur in winter and spring seasons. It was also proved that cattle lesion with Cryptosporidium agent depends on its age. During investigation the following activities have been conducted: comparative analysis of methodic dealing with laboratory researchers; peaked effectiveness in the method of alive diagnostic in Cryptosporidiosis calves dealt with feces smear dyeing with for microscopic testing in accordance with Cester was confirmed. Their advantages in comparison with other dyeing methods were denoted. Comparative analysis of Toltarocsis and Toltarocsis with Immunebacterium-D was conducted and defined its effectiveness. The influence of treatment measures on morphological, biological and immune indexes of calves’ blood was tested. General and specific prophylactic measures which helped avoid cattle lesion with Cryptosporidium was proposed and implemented
Keywords: криптоспоридіоз; телята; Cryptosporidium parvum; поширення; методи діагностики; толтарокс та імунобактерин-D; ryptosporidium; calves; expansion; diagnostic methods